2012
DOI: 10.1007/s00011-011-0420-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-like weak inducer of apoptosis and its potential roles in lupus nephritis

Abstract: TWEAK plays a key role in the pathogenesis of LN through activation of multiple down-signaling pathway, inducing proinflammatory cytokines and chemokines, affecting cell proliferation/apoptosis and inducing renal IgG deposition. TWEAK blockade may be a novel therapeutic approach to reducing renal damage in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Here, we show these effects in tumor cell lines and that a TWEAK blockade with an anti-TWEAK mAb, RG7212, results in significant tumor growth inhibition (TGI) in multiple tumor models expressing Fn14. These in vitro and in vivo data are consistent with tumor-promoting effects shown with other TNF family receptors lacking death domains (19,20) and with TWEAK data in disease models in animals and pathologic conditions in humans (21,22).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Here, we show these effects in tumor cell lines and that a TWEAK blockade with an anti-TWEAK mAb, RG7212, results in significant tumor growth inhibition (TGI) in multiple tumor models expressing Fn14. These in vitro and in vivo data are consistent with tumor-promoting effects shown with other TNF family receptors lacking death domains (19,20) and with TWEAK data in disease models in animals and pathologic conditions in humans (21,22).…”
Section: Introductionsupporting
confidence: 86%
“…In contrast to data showing TWEAK proinflammatory, proangiogenic, and proliferation-inducing effects in disease models in animals (5,(23)(24)(25) and association of pathway activation with human disease (21,22,(26)(27)(28), some published in vitro studies have shown that TWEAK induces apoptosis via upregulation of TNFa (29) or in combination with IFNg in a small number of tumor cell lines (8). In the absence of IFNg, apoptosis induction was modest (30) or required relatively high TWEAK concentrations (29).…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, it has been reported that a short course of anti-tumor necrosis factor therapy with infliximab had a prolonged beneficial effect on proteinuria in LN (5). More recently, other proinflammatory molecules, such as TWEAK, have emerged as promising targets in LN (6). Hopefully, clinical trials with such targets will deliver the clinical outcomes we need.…”
Section: To the Editormentioning
confidence: 99%
“…LN is a common and serious complication of systemic lupus erythematosus patients, and is considered to be the crucial factor in the prognosis of the disease (Liu and Zhou, 2012). Immune cells, cytokines, and epigenetic factors have all been recently implicated in LN pathogenesis (Schwartz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%